Application of modern drilling machines in transport construction - Grinchar N.G.; Shoshin A.S.; Chalova M.Yu. (Научно-технический вестник Брянского государственного университета)
The broad scale of the plan for the development of the Far North, Siberia, provides for the annual development of hundreds of millions of cubic meters of permafrost soils and rocks, most of which require the use of drilling and blasting operations. The most time consuming process of preparing rocks for excavation is the creation of wells. Drilling of permafrost soils, soils with rock inclusions, monolithic and fractured rocks requires careful analysis and detailed calculations for each type of rock. It should also be borne in mind that the harsh climatic conditions of work in the Far North, open mining fields, also imply a significant distance from any settlements, therefore, based on the above factors, special attention should be paid to investigate the problems of mobility and reliability of tractor drilling rigs. This article discusses the use of modern drilling machines, provides a comparison of a tractor drilling rig with a mechanical drive of a drill string with a machine with a hydraulic drive, lists the factors confirming the feasibility of using a hydraulic drive of a drilling string, examines the results of tests of drilling various rocks, as well as the effect of rock structure on vibrations pressure and increase in the flow rate of hydraulic fluid in the drive system of the machine.